Catalog of Geomagnetic Storms with Dst Index ≤ −50 nT and Their Solar and Interplanetary Origin (1996–2019) - Rositsa Miteva; Susan W. Samwel (Atmosphere, 2023)
We present a comprehensive catalog of geomagnetic storms (GSs) with a Dst index <semantics>≤−50</semantics> nT detected during solar cycles (SCs) 23 and 24 (1996–2019). About 550 events were identified in the Kyoto database and used as a starting point for this study. The solar origin of the GSs, in terms of coronal mass ejections (CMEs), solar flares (SFs), and in situ-observed energetic particles, was identified where possible using temporal constraints and wide Earth-directed ejecta. In addition, any accompanied interplanetary (IP) sources, such as ICMEs and IP shock waves detected at 1 AU, are also considered. The resulting occurrence rates and correlation plots are presented and discussed in the space weather framework.